High‐molecular‐weight polyisobutylenes (PIBs) and PIB networks from liquid PIBs by thiol‐ene clicking. Issue 11 (2nd April 2019) - Kurnaz, Elif; Helvacioglu, Ekmel; Kekec, Nur Cicek; Nugay, Nihan; Nugay, Turgut; Kennedy, Joseph P.
ABSTRACT: We report the synthesis of high‐molecular‐weight linear polyisobutylenes (PIBs) and PIB networks from low‐molecular‐weight PIB by thiol‐ene click chemistry. Thus, liquid allyl‐telechelic PIB was reacted with small di‐ and tri‐thiols, and the thiolated intermediates chain‐extended by UV‐ or thermally induced free radical initiation to linear and crosslinked products. PIB networks were also prepared by crosslinking SH‐telechelic PIB with a small triallyl compound. Linear products were characterized by 1 H NMR spectroscopy and GPC, and networks by FTIR spectroscopy, extractables, swelling, and permanent set. The effect of reaction conditions (nature of thiol chain extender, concentration of photo‐ and thermal initiators, UV radiation time, and reagent concentrations) on chain extension and crosslinking was investigated. Under well‐defined conditions high‐molecular‐weight PIBs and tight PIB networks were prepared. Thiol‐ene click chemistry provides novel thiolated PIB derivatives and is a useful strategy for the convenient preparation of high‐molecular‐weight rubbery PIBs and tight PIB networks from low‐molecular‐weight PIB precursors. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019 Abstract : The authors synthesized high‐molecular‐weight polyisobutylenes (PIB) from liquid CH2 CH‐CH2 ‐telechelic PIB + small dithiols by thiol‐ene clicking. By the same strategy, the authors also prepared tight PIB networks from CH2 CH‐CH2 ‐telechelic PIB + small trithiol, and HS‐telechelic PIB + triallyl crosslinkers (see image). The products were characterized and some properties examined.